Sahabat Pemberani: An Animation Series to Enhance Children’s Social Values of Manners - Permata Cahyaningtyas, Andarini; Fironika Kusumadewi, Rida; Faizul Mas'ud, Isna (KnE Social Sciences, 2022)
Animation is a robust gate to convey and teach the values of life for children, and one of those is the social values of manners. This study aims to determine the social values of manners contained in a children series called Sahabat Pemberani. The research was conducted using the descriptive qualitative method. The data sources were eight episodes of Sahabat Pemberani, two episodes are from the first season, and the rest is from the second season. The data were collected through observation sheets and analyzed through three phases: data reduction, data display, and verification. The validity of the data was checked using increased perseverance and peer discussion techniques. The study’s result showed that there are twelve social values of manners found in Sahabat Pemberani. All those values were spread in eight episodes, and these will be great examples for children on how to behave appropriately. Keywords: Social values, Manners, Animation series, Sahabat Pemberani